Characteristics of waste catalyst reused as latent hydraulic materials. Issue 1 (16th November 2011) - Lin, Kae‐Long; Wu, Hsiu‐Hsien; Chao, Sao‐Jeng; Cheng, An; Hwang, Chao‐Lung
<x xml:space="preserve">Abstract</x> This study investigated the pozzolanic reactions and engineering properties of waste catalyst (WC)‐blended cements in relation to various replacement ratios (0–40%). The latent hydraulic characteristics were evaluated at various curing ages by examining the hydration products and compressive strength of the waste catalyst blended cement (WCBC) pastes. The results indicate that the WC contained Al2O3 (59 w/w %), SiO2 (39 w/w %), and CaO (0.1 w/w %) and the pozzolanic activity index of the WC was 117%. The heavy metal leaching concentrations all met the Taiwan EPA regulatory limits. The early compressive strength of the resultant blended cement pastes (1–28 days) was lower than that of the ordinary Portland cement (OPC); however, WCBC pastes with a replacement of cement by up to 20% showed a later compressive strength (60–90 days) similar to that of OPC paste. The hydrated WCBC pastes were similar to OPC pastes in terms of hydration product composition. The main hydration products in the WCBC pastes were Ca(OH)2 and C‐S‐H (Tobermorite). The results indicate that it is indeed feasible to use WC as one of the mineral components for cement. © 2011 American Institute of Chemical Engineers Environ Prog, 32: 94–98, 2013.